Relationship between production of 3-indoleacetic acid and peroxidase-laccase activities depending on the culture periods in Funalia trogii (Trametes trogii) - Unyayar, S; Unal, E; Unyayar, A (Folia microbiologica, 2001)
The relationship between production of 3-indoleacetic acid (IAA) and peroxidase and laccase activity was investigated in white-rot fungus Funalia trogii (Trametes trogii). F. trogii produced IAA and peroxidase and laccase as both primary metabolite and secondary metabolite; the levels of IAA may be influenced by peroxidase and laccase. A correlation exists between the levels of IAA and peroxidase-laccase activity.
Keywords: lakasa; peroxidasa; Polyporales; Laccase; Peroxidase; kyseliny indoloctové; Indoleacetic Acids; Oxidoreductases; oxidoreduktasy